Decision Support System for the INAIMA AIS Officer of the Year Award using AHP-TOPSIS Method - Dewa Gede Edi Putra; M. Ramaddan Julianti; Siti Maesaroh (JURNAL SISFOTEK GLOBAL, 2023)
The professional organization of the Indonesian Aeronautical Information Management Association always tries to increase the motivation of its members. One of INAIMA's work programs to make this happen is to elect the AIS Officer of The Year. In practice, the selection of AIS Officer of the Year is still carried out by collecting data manually without using a system so that it takes longer time to process the data. Furthermore, the results obtained from the election are also not objective because there is no method of calculating the criteria for evaluating candidates, so a decision support system is needed that can provide objective election results and is able to speed up the evaluation process. The method used in designing this decision support system is the SDLC (Software Development Life Cycle) where the stages include planning, analysis, design, implementation, testing, and maintenance. ). The calculation of the weight value of the criteria and alternatives on the system uses the AHP-TOPSIS method. The result is a web-based decision support system that is able to provide a more precise and objective assessment of candidates.